Medicinal Chemistry Aspects of Isoxazole Analogues as Anti-tubercular Agents - Singh, Harshwardhan; Kumari V.S., Anila; Singh, Ankit K.; Kumar, Adarsh; Kumar, Pradeep (Current Organic Chemistry, 2023)
Tuberculosis (TB) is the major cause of mortality around the world and one of the most common diseases linked to AIDS. Due to the emergence of multi-drug resistance, extensive drug resistance, and total drug resistance strains, TB has become a difficult disease to treat. Isoxazole scaffold shows a wide range of biological activities, including anticancer, antibacterial, anti-tubercular, antiviral, and anti-inflammatory activities etc. Several isoxazole derivatives have been produced and few of them have shown comparable anti-tubercular activity with standard drugs. In this review, we have focused on reported isoxazole derivatives having anti-tubercular activity and summarized their structure-activity relationship.
Keywords: Mycobacterium tuberculosis